1999
DOI: 10.1002/(sici)1096-9861(19990607)408:3<318::aid-cne2>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Sequential developmental acquisition of cotransmitters in identified sensory neurons of the stomatogastric nervous system of the lobsters,Homarus americanus andHomarus gammarus

Abstract: We studied the developmental acquisition of three of the cotransmitters found in the gastropyloric receptor (GPR) neurons of the stomatogastric nervous systems of the lobsters Homarus americanus and Homarus gammarus. By using wholemount immunocytochemistry and confocal microscopy, we examined the distribution of serotonin‐like, allatostatin‐like, and FLRFNH2‐like immunoreactivities within the stomatogastric nervous system of embryonic, larval, juvenile, and adult animals. The GPR neurons are peripheral sensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
2
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 57 publications
3
71
2
2
Order By: Relevance
“…These data are consistent with a number of previous studies in both C. borealis and other species that reported immunostained punctate structures for amines and peptides in the stn-son junction (Marder et al, , 1987Callaway et al, 1987;Mortin and Marder, 1991;Kilman et al, 1999;Skiebe, 1999;Skiebe et al, 1999). These punctate structures are found within the nerve where most of the modulatory axons coming from the CoGs and the OG are located.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These data are consistent with a number of previous studies in both C. borealis and other species that reported immunostained punctate structures for amines and peptides in the stn-son junction (Marder et al, , 1987Callaway et al, 1987;Mortin and Marder, 1991;Kilman et al, 1999;Skiebe, 1999;Skiebe et al, 1999). These punctate structures are found within the nerve where most of the modulatory axons coming from the CoGs and the OG are located.…”
Section: Resultssupporting
confidence: 92%
“…2 A) (Marder et al, , 1987Kilman et al, 1999;Skiebe, 1999;Skiebe et al, 1999), suggesting that this region is a potential site for synaptic and/or modulatory interactions among fibers traveling in the stn. We labeled the fibers projecting from the ion to the stn by backfilling the ion fibers with neurobiotin and then immunostaining these preparations for synaptotagmin (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuromodulatory systems involved in the control of central pattern generators (CPGs) have been extensively studied in terms of neuronal population, neurotransmitter phenotype, and alteration of network activity. A large body of work has been devoted to the progressive developmental acquisition of projection neurons using retrograde dye migration (Cabana and Martin, 1984;van Mier and ten Donkelaar, 1984;Okado and Oppenheim, 1985;Kudo et al, 1993) and of neuromodulatory substances using immunocytochemistry (Senba et al, 1982;Commissiong, 1983;Sako et al, 1986;van Mier et al, 1986;Rajaofetra et al, 1989;Pindzola et al, 1990;Fenelon et al, 1998aFenelon et al, , 1999Kilman et al, 1999). Using these approaches, it has been concluded that progressive acquisition of neuromodulatory substances by a target network is associated with axonal ingrowth of descending neurons (Sako et al, 1986;van Mier et al, 1986;Pindzola et al, 1990).…”
Section: Abstract: Central Pattern Generator; Development; Modulatormentioning
confidence: 99%
“…Using these approaches, it has been concluded that progressive acquisition of neuromodulatory substances by a target network is associated with axonal ingrowth of descending neurons (Sako et al, 1986;van Mier et al, 1986;Pindzola et al, 1990). However, some studies seem to indicate that projection neurons may reach their targets before expressing their adult neurotransmitter complement (Henderson, 1991;Kilman et al, 1999). To investigate whether such ontogenetic processes may exist in descending systems, we combined retrograde dye migration to label embryonic neurons reaching their target networks, and immunocytochemical detection of neuromodulatory substances.…”
Section: Abstract: Central Pattern Generator; Development; Modulatormentioning
confidence: 99%